BENEFICIAL EFFECTS OF AN HYDROETHANOLIC EXTRACT OF SMALLANTHUS SONCHIFOLIUS LEAVES ON THE METABOLIC CHANGES IN DIABETIC RATS - SILMARA BARONI,; JURANDIR FERNANDO COMAR,; FUMIE SUZUKI KEMMELMEIER,; MÁRCIO SHIGUEAKI MITO,; JULIANA OLIVEIRA DE MELO,; BRUNO AMBRÓSIO DA ROCHA,; CIOMAR APARECIDA BERSANI-AMADO, (International Journal of Pharma and Bio Sciences, 2014)
In this study the anti-hyperglycemic effect of the hydroethanolic extract of Smallanthus sonchifolius leaves (yacon extract) in streptozotocin-induced type 1 diabetic rats (SZT i.p, 50 mg/kg) was characterized, with emphasis on the metabolic changes found in this experimental model. Diabetic and normal rats received extract (400 mg/kg) or water by the oral route for 30 days. At the end of the treatment, rats were fasted for 15 h and blood samples were collected for the determination of glycemia. The activity of glucose-6-phosphate dehydrogenase, transaminases (ALT and AST), the glycogen contents of the liver and muscle, and glucose release in substrate-free perfused liver were quantified. The treatment with the extract reduced glycemia in diabetic animals, restored the activity of glucose-6-phosphate dehydrogenase and AST, decreased the glycogen content of the liver and skeletal muscle, and decreased glucose release in the perfused liver. The results support the beneficial effects of the extract on some metabolic changes of SZT-induced diabetes in rats.